An Italy-China Collaboration for Promoting Public Mental Health Recommendations During the COVID-19 Pandemic - Scattoni, Maria Luisa; Starace, Fabrizio; de Girolamo, Giovanni; Xia, Jun (Frontiers in Public Health, 2021)
The rapid evolution of SARS-Cov 2 emergency involved Italy as the first European country. Meanwhile, China was the only other country to experience the emergency scenario, implementing public health recommendations and raising concerns about the mental health of the population. The Italian National Institute of Health (Istituto Superiore di Sanità [ISS]) reviewed relevant scientific literature in mental health to evaluate the best clinical practices and searched for the collaboration with the World Health Organization, World Psychiatry Association, and China to support the public health system in a phase of acute emergency. This process permitted to define organizational and practical-operational Italian guidelines for the protection of health care workers’ wellbeing. These guidelines have been extensively disseminated within the Italian territory for maximum stakeholder utilization.